2022
DOI: 10.1186/s12915-022-01380-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of macrophage inflammatory function through selective inhibition of the epigenetic reader protein SP140

Abstract: Background SP140 is a bromodomain-containing protein expressed predominantly in immune cells. Genetic polymorphisms and epigenetic modifications in the SP140 locus have been linked to Crohn’s disease (CD), suggesting a role in inflammation. Results We report the development of the first small molecule SP140 inhibitor (GSK761) and utilize this to elucidate SP140 function in macrophages. We show that SP140 is highly expressed in CD mucosal macrophage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…It has been reported that SNPs in the SP140 locus have been strongly linked to diverse autoimmune and inflammatory diseases such as multiple sclerosis (MS) [11] and Crohn's disease (CD) [12]. In addition, our previous study demonstrated upregulated expression of SP140 in a range of inflammatory diseases such as CD, rheumatoid arthritis (RA), and systemic lupus erythematosus [10], implicating SP140 in immune-mediated pathogenesis. SP140 is an epigenetic reader protein harboring a bromodomain (Brd) [12,13]; Brd recognizes acetylated lysine residues on histone tails and regulates gene expression through mechanisms that modulate DNA accessibility to transcription factors (TFs) and the transcriptional machinery [14,15].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…It has been reported that SNPs in the SP140 locus have been strongly linked to diverse autoimmune and inflammatory diseases such as multiple sclerosis (MS) [11] and Crohn's disease (CD) [12]. In addition, our previous study demonstrated upregulated expression of SP140 in a range of inflammatory diseases such as CD, rheumatoid arthritis (RA), and systemic lupus erythematosus [10], implicating SP140 in immune-mediated pathogenesis. SP140 is an epigenetic reader protein harboring a bromodomain (Brd) [12,13]; Brd recognizes acetylated lysine residues on histone tails and regulates gene expression through mechanisms that modulate DNA accessibility to transcription factors (TFs) and the transcriptional machinery [14,15].…”
Section: Introductionmentioning
confidence: 90%
“…Speckled 140 KDa (SP140) is a nuclear body protein predominantly expressed in immune cells [9,10]. The expression of SP140 is induced during microbial infections and in response to inflammatory stimuli [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential methylation of the speckled 140 kDa protein (SP140) observed in the peripheral blood mononuclear cells of patients with CD, as well as the fact that reduced SP140 expression in intestinal biopsies correlates with a good anti-TNF response, suggests a role for SP140 in IBD [ 52 ]. SP140 functions as an epigenetic reader, the inhibition of which can prevent the generation of inflammatory macrophages as well as the regulation of proinflammatory and CD-related gene expression [ 52 , 53 ]. Homologous to the speckled-protein family, the autoimmune regulator AIRE is a master regulator of central tolerance, which links transcription factors and epigenetic machinery by driving the expression of tissue-specific T-cell antigens.…”
Section: Histone Modifications and Chromatin Organizers As Influencer...mentioning
confidence: 99%
“…14 Furthermore, C3HeB/FeJ mice do develop necrotizing granulomas, especially when infected with hypervirulent Mtb strains of the W-Beijing lineage. 15 A single gene that confers the extreme susceptibility and necrotic lesions of C3HeB/FeJ mice has been identified as Sp140 , an epigenetic regulator with chromatin-binding domains that can influence inflammatory gene transcription, 16 and Sp140 -/- mice on a C57BL/6 background exhibit similar TB susceptibility and pathology phenotypes as C3HeB/FeJ mice. 17 Use of these mouse models has led to the identification of critical signaling pathways that regulate Mtb infection outcomes, including type I IFN vs IL-1, as well as insights into the temporal processes driving inflammation and disease: neutrophil recruitment, cellular death, pDC sensing, and IFN production/signaling.…”
Section: Introductionmentioning
confidence: 99%